TRAF3: Guardian of T lymphocyte functions - Hornick, Emma L.; Bishop, Gail A. (Frontiers in Immunology, 2023)
Tumor necrosis factor receptor (TNFR)-associated factor 3 (TRAF3) is an adapter protein with many context-specific functions. Early studies of lymphocyteTRAF3 hinted at TRAF3’s importance for T cell function, but elucidation of specific mechanisms was delayed by early lethality of globally TRAF3-/- mice. Development of a conditional TRAF3-deficient mouse enabled important descriptive and mechanistic insights into how TRAF3 promotes optimal T cell function. Signaling through the T cell antigen receptor (TCR) fails to induce normal proliferation and survival in TRAF3-/- T cells, and TCR-activated cells in vitro and in vivo have deficient cytokine production. These defects can be traced to incorrect localization and function of negative regulatory phosphatases acting at different parts of the signaling cascade, as can dysregulated effector responses and memory T cell homeostasis in vivo and an enlarged regulatory T cell (Treg) compartment. The important regulatory activity of TRAF3 is also evident at members of the TNFR superfamily and cytokine receptors. Here, we review significant advances in mechanistic understanding of how TRAF3 regulates T cell differentiation and function, through modulation of signaling through the TCR, costimulatory receptors, and cytokine receptors. Finally, we briefly discuss the recent identification of families carrying single allele loss-of-function mutations in TRAF3, and compare the findings in their T cells with the T cell defects identified in mice whose T cells completely lack T cell TRAF3. Together, the body of work describing TRAF3-mediated regulation of T cell effector function and differentiation frame TRAF3 as an important modulator of T cell signal integration.